Comparative account of induced breeding of Indian major carps with ovaprim, ovatide, wova- FH and carp pituitary extract - Rath, S C; Sarkar, S K; Gupta, S D; Sarangi, N (The Indian Journal of Animal Sciences, 2007)
Indian major carps, viz. Catla catla, Labeo rohita and Cirrhinus mrigala were induced bred in eco-carp hatcheries with 3 different GnRH based synthetic inducing agents, viz. ovaprim, ovatide, wova - FH (OOW) and carp pituitary extract (CPE). The breeding performance of the these agents are compared. Breeding response, mean spawning fecundity, mean spawn recovery rate of OOW ranged between 90 and 100%, 1.30x105 and 1.79x105 , 0.97x105 and 1.34x105 respectively, Whereas the above parameters in the same sequence in CPE-administered fish were 77 and 84%, 1.04x105 and 1.30x105 and 0.65x105 and 0.90x105 respectively. The latency period (time between administration of inducing agent and initiation of spawning) of OOW and CPE-administered brood varied between 5-7 h and 10-13 h respectively. The effective spawning period for both the groups are worked out as 2-3 h and 5-6 h respectively. The GSI of the spent female on the day of spawning ranged between 2.18-2.58 in OOW administered individuals and 5.27-6.28 in CPE group. The histomorphology of spent ovaries retained more number of unspawned oocytes in the female brood of CPE- induced breeding than that of OOW. The pituitary cyanophiis of proximal pars distalis (PPD) was found to be hyperactive and degranulated in ovaprim, ovatide and wova-FH administerd brood. Whereas CPE-administered pituitary was found at par with non-induced individuals